1993
DOI: 10.1161/01.res.72.2.387
|View full text |Cite
|
Sign up to set email alerts
|

NG-nitro L-arginine methyl ester and other alkyl esters of arginine are muscarinic receptor antagonists.

Abstract: Analogues of L-arginine with modifications at the terminal guanidino nitrogen and/or the carboxyl terminus of the molecule have been widely used for their ability to inhibit the production of nitric oxide and are thought to be competitive antagonists of nitric oxide synthase. The present studies were designed to test the possibility that these agents are also muscarinic receptor antagonists. Acetylcholine produced concentration-dependent contraction of endothelium-denuded rabbit coronary artery as well as isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
221
6
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(238 citation statements)
references
References 21 publications
10
221
6
1
Order By: Relevance
“…Similar results are observed when the availability of NO is reduced by the NO scavenger, carboxy PTIO (Summy-Long JY and Bui V, unpublished data). This is an important comparison to interpret NO's effects on hormone secretion because it has been shown that, in addition to inhibiting NOS activity, L-NAME also has antimuscarinic effects (30). Thus, our studies indicate that NO is tonically produced in the forebrain during euvolemic isosmotic conditions to inhibit secretion of both hormones from the magnocellular system.…”
Section: No and Neurohypophyseal Hormones Basal Conditionsupporting
confidence: 50%
“…Similar results are observed when the availability of NO is reduced by the NO scavenger, carboxy PTIO (Summy-Long JY and Bui V, unpublished data). This is an important comparison to interpret NO's effects on hormone secretion because it has been shown that, in addition to inhibiting NOS activity, L-NAME also has antimuscarinic effects (30). Thus, our studies indicate that NO is tonically produced in the forebrain during euvolemic isosmotic conditions to inhibit secretion of both hormones from the magnocellular system.…”
Section: No and Neurohypophyseal Hormones Basal Conditionsupporting
confidence: 50%
“…Before reaching conclusions about the role of NO in the cerebrovascular reactions under study, some discussion about the effects of L-NAME not attributable to NOS inhibition is needed, since L-NAME has been shown to be a muscarinic antag onist (Buxton et a!., 1993). However, the seizures induced by KA mostly involve glutamatergic path ways rather than cholinergic pathways, and in the present experiments, the seizure intensity (electro graphic and behavioral events) was not reduced by L-NAME.…”
Section: )mentioning
confidence: 60%
“…14 It is therefore possible that nonspecific vascular effects may not be limited to ADMA in particular but may also be extended to L-arginine analogues in general. Multiple actions of L-arginine analogues have been reported, which include inhibition of cytochrome c reduction, 13 endothelial generation of superoxide anions, 40 antagonism of muscarinic acetylcholine receptors, 12 impairment of urea cycle in which L-arginine is a substrate, 41 and inhibition of the endothelium-independent relaxation induced by amiloride (an inhibitor of Na ϩ -H ϩ exchange) and dibutyryl cAMP (a membranepermeable cAMP analogue). 42 Thus, multiple mechanisms other than simple inhibition of endothelial NO synthesis appear to be involved in the long-term vascular effects of L-arginine analogues.…”
Section: Multiple Nonspecific Effects Of L-arginine Analoguesmentioning
confidence: 99%
“…8,9 See cover However, it is controversial whether these vascular effects of L-NAME are caused primarily by the inhibition of endothelial NO synthesis for the following reasons: first, the importance of endothelium-derived NO decreases as the vessel size becomes smaller, 10 whereas L-NAME-induced vascular lesions are prominent at microvascular levels; 8 second, long-term treatment with L-NAME does not reduce eNOS activity; 11 third, multiple actions of L-NAME other than simple inhibition of NO synthesis have been reported. 12,13 The most appropriate way to address this issue is to use mice that are deficient in the eNOS gene and to examine whether long-term treatment with L-NAME causes coronary vascular lesions in those mice. We have recently shown that treatment with L-NAME causes a comparable extent of coronary arteriosclerotic lesions in wild-type and eNOS-KO mice.…”
mentioning
confidence: 99%